Efficiency and audit fees: evidence from the U.S. manufacturing firms / Qian Long Kweh, Yee Chuann Chan and Wei-Kang Wang - Kweh, Qian Long; Chan, Yee Chuann; Wang, Wei-Kang (2013)
This study examines the association between firm efficiency and audit fees for the period from 2004 to 2009. In the first stage, data envelopment analysis (DEA) technique is used to evaluate the level of efficiency of the U.S. manufacturing firms. Next, the DEA efficiency score is included as an explanatory variable in the audit fees model of this study. This study provides empirical evidence that firm efficiency is significantly and negatively related to audit fees, suggesting that firm efficiency is an effective determinant of audit fees. The negative relation supports the view that more efficient firms pay lower audit fees. In sum, firms can improve their efficiency to get lower audit fees due to the lower audit risk exposure.